Mechanical Characteristics Testing of Biodegradable Ramie Fiber Reinforced Polylactic Acid (PLA) Fabricated with Hot-Press Molding - Sujarwadi, Roni; Soemardi, Tresna Priyana (Proceeding International Conference on Science and Engineering, 2020)
In this research, composite material was fabricated from both renewable resources and biodegradable materials: ramie woven fabric as reinforcement and 3D printed polylactic acid (PLA) filament as resin matrix. The laminate composites were produced using a film stacking method and processed using hot-press molding. The mechanical properties of woven ramie fabric, PLA matrix, and laminate composites were investigated. It is shown that the breaking force of the plain woven ramie fabric in the warp direction was greater than in the weft direction. Further, the tensile and impact properties of laminate at warp direction higher than weft direction when ramie fabric reinforcement is used. In addition, scanning electron microscopy examination of laminate composite showed good bonding between ramie fiber and PLA matrix. In summary, laminated composites based on polylactic acid and woven ramie fabric display good performance capability, which can use for the development of engineering applications.